Interest Rates, Credit Rationing, and Investment in Developing Countries - Nkusu, Mwanza (Washington, D.C. : International Monetary Fund, 2003)
This paper examines the impact of interest rates and inflation on bank loans and investment within a framework that mimics the financial sectors prevailing in most low-income developing countries. The paper emphasizes the importance of treating the lending and deposit rates of interest as distinct parameters in investment equations. The spread between the two rates is indicative of default risk and has a negative impact on incremental loan amounts associated with higher lending rates, in particular in economies with flawed institutions. The model presented in the paper highlights the importance of promoting macroeconomic stability and upgrading institutions and informational infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet